Design and implementation of a multiband digital filter using FPGA to extract the ECG signal in the presence of different interference signals. (1st July 2015) - Aboutabikh, Kamal; Aboukerdah, Nader
Abstract: In this paper, we propose a practical way to synthesize and filter an ECG signal in the presence of four types of interference signals: (1) those arising from power networks with a fundamental frequency of 50 Hz, (2) those arising from respiration, having a frequency range from 0.05 to 0.5 Hz, (3) muscle signals with a frequency of 25 Hz, and (4) white noise present within the ECG signal band. This was done by implementing a multiband digital filter (seven bands) of type FIR Multiband Least Squares using a digital programmable device (Cyclone II EP2C70F896C6 FPGA, Altera), which was placed on an education and development board (DE2-70, Terasic). This filter was designed using the VHDL language in the Quartus II 9.1 design environment. The proposed method depends on Direct Digital Frequency Synthesizers (DDFS) designed to synthesize the ECG signal and various interference signals. So that the synthetic ECG specifications would be closer to actual ECG signals after filtering, we designed in a single multiband digital filter instead of using three separate digital filters LPF, HPF, BSF. Thus all interference signals were removed with a single digital filter. The multiband digital filter results were studied using a digital oscilloscope to characterize input and output signals in the presence of differing sinusoidal interference signals and white noise. Highlights: In this research, the ECG signal simulator, and the multiband digital filter is successfully designed. The designed filter has a linear phase response, so this reduces the filtered signal distortions and makes the diagnosis operation close to the real case. The practical experiments ensure that the possibility of using this type of filters in the ECG devices.